Investigation of the deterioration degree of parchment marked with iron gall inks - Georgia Velivasaki (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The study aims at determining the damage extend of parchment in the presence of iron-gall inks under artificial ageing conditions. Samples of parchment from goat skin were marked with two different iron-gall inks prepared according to simple traditional recipes, both containing iron sulfate and Gallic acid, while one of them additionally contained gum. The samples were then subjected to artificial ageing at 80oC in the presence of humidity (RH=80%). For a reliable evaluation of results, reference samples of neighboring parchment areas (no ink, identical ageing conditions) were analyzed in parallel with SEM-EDAX, FTIR and MHT thermal analysis.